Northeast monsoon effect on ultra high frequency (UHF) signal attenuation at Kusza observatory - Nor Hazmin, Sabri; Sharifah Nurul Aisyah, Syed Zafar; Roslan, Umar; Roshidah, Mat (2018)
Northeast (NE) monsoon season in Malaysia was developed due to conjunction with cold air outbreaks from Siberia produce heavy rains, strong wind, and high humidity. This weather condition can affect the radio signal transmission which is crucial to spectrum user. This work investigates the effect of the wet season due to Northeast season on radio signal power within Ultra High Frequency (UHF) band at KUSZA Observatory (KO). Three of weather parameters (wind speed, humidity and rain rate) was considered with the radio signal variation. Measurement of these weather parameters and radio signal power level (dBm) were collected using weather station and spectrum analyzer respectively. From the result obtained, we found that wind speed played a role in radio signal attenuation indirectly. The combination of wind speed (km/h) along with high humidity (%) and rain rate(mm/s) during NE monsoon season have given a significant impact to a radio signal. These findings is useful to radio astronomer to determine the best period for radio astronomical observation with minimum interference considering weather condition. This study will also beneficial to spectrum user such as mobile telecommunication, wireless internet and radio broadcasting in managing and improving their services.